Orientação solar e conforto lumínico. Análise das condições ambientais e opinião dos usuários - Lima, Amanda Vieira Pessoa (2019)
In buildings, the surroundings and the orientations of the façades influence the lighting and the indoor environment quality. In office environments, lighting is one of the influential conditions for visual comfort, health, well-being and worker productivity. From this perspective, the work aims to identify the impact of the orientation of the main façade on lighting levels and user satisfaction. Measurements were made in two buildings with similar architectural characteristics, the main difference between them is the orientation of the main façade, and they are located in the center of João Pessoa, whose predominant climate is the hot-humid. In the study, variables related to visual comfort and user satisfaction were analyzed. In total the analysis includes 219 measured jobs, with questionnaires answered by their respective users. The results show significant differences between the two buildings, where the east-facing building has illuminance levels (maximum 2620 lux) and user dissatisfaction (45.58%) with natural light, higher than the north and south-oriented building, with 18.07%. It was also found that despite the benefits of window proximity in worker comfort, in the hot-humid tropical climate, when the window is located on the east façade, negative aspects in light comfort are detected. The results show that the main façades facing North and South orientation present better indoor lighting conditions.